Controls on crustal seismicity segmentation on a local scale in the Southern Central Andes. (June 2022) - Olivar, Julián; Nacif, Silvina; García, Hector; Fennell, Lucas; Heit, Benjamin; Folguera, Andrés
Abstract: The Argentine Andes between 34° and 36°S comprise a region that lies immediately south of the transition from the Chilean-Pampean flat-slab to a normal subduction segment. Several key changes take part through this area, such as a westward shift of the magmatic arc front, the end of Paleozoic outcrops of the Frontal Cordillera denoting a decline in exhumation, the change in strike of the orogenic belt, and a ∼2 km decrease in maximum and mean topography. We assess the associated segmentation of the deformation by studying the local seismicity. By analyzing one year of seismological data obtained from a local network, we found a significant shift in the low magnitude (M < 3) crustal seismicity pattern at ∼34.8°S. To the north, most events occur along the topographic front. In contrast, to the south, no events are observed in the frontal region but are instead located closer to the Andean axis. In addition, we used gravity data to determine elastic thickness in the region to compare crustal seismic activity with the pattern of crustal rigidity. We discuss this and other geological, tectonic, and climatic factors as possible controls on seismicity segmentation. We do not find a controlling role by neither elastic thickness nor precipitation patterns. Instead, we propose a thermal contrast due to the volcanic arc's geometry, and differing stress transfer from the subducting slab owing to mantle wedge heterogeneities, as the main active controls on the seismicity distribution; modulated by a passive control by pre-Andean rheological features of the crust. Highlights: Crustal seismicity in the Southern Central Andes is studied with a local network. A shift in the spatial pattern is found across the Atuel river, Mendoza, Argentina. To the north, there is seismic activity in the Andean front. Southward, seismicity is absent in the front but only present near the inner region. Thermal contrast and variable stress transfer from the slab are the main controls.